2022
DOI: 10.1186/s12576-022-00833-5
|View full text |Cite
|
Sign up to set email alerts
|

The olfactory bulb coordinates the ventral hippocampus–medial prefrontal cortex circuit during spatial working memory performance

Abstract: Neural oscillations synchronize the activity of brain regions during cognitive functions, such as spatial working memory. Olfactory bulb (OB) oscillations are ubiquitous rhythms that can modulate neocortical and limbic regions. However, the functional connectivity between the OB and areas contributing to spatial working memory, such as the ventral hippocampus (vHPC) and medial prefrontal cortex (mPFC), is less understood. Hence, we investigated functional interaction between OB and the vHPC–mPFC circuit during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 63 publications
0
16
0
Order By: Relevance
“…A prior study involving healthy animals demonstrated that coherency between the OB and the PFC-HPC circuit increased during correct task performance. 11 This indicates that OB electrical stimulation brought the working memory circuit’s activity closer to that of healthy animals. This impact of olfactory pathway stimulation was also evident in comatose patients.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…A prior study involving healthy animals demonstrated that coherency between the OB and the PFC-HPC circuit increased during correct task performance. 11 This indicates that OB electrical stimulation brought the working memory circuit’s activity closer to that of healthy animals. This impact of olfactory pathway stimulation was also evident in comatose patients.…”
Section: Discussionmentioning
confidence: 94%
“…The OB plays a significant role in working memory performance. 11,12 A significant mechanism through which the OB potentially impacts working memory is nasal breathing. 38,39 The OB acts as a gateway, allowing nasal respiration to dynamically modulate brain activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study shows stronger activation in the dorsal taenia tecta than in the ventral taenia tecta in response to an odorant, which could be explained by an indirect projection from the entorhinal cortex (Cousens, 2020). Research is underway to learn more about the role of the taenia tecta (Salimi et al, 2022; Shiotani et al, 2020).…”
Section: Description Of the Olfactory Striaementioning
confidence: 99%